Dynamics of a subtropical population of the purse crab Persephona punctata (Decapoda: Brachyura: Leucosiidae) in Southeastern Brazil - Perroca, Julia Fernandes [UNESP]; Herrera, Daphine Ramiro [UNESP]; Castilho, Antonio Leao [UNESP]; Costa, Rogerio Caetano da [UNESP] (Soc Brasileira Carcinologia, 2020)
This study investigated the population dynamics of Persephona punctata with emphasis on population structure, sex-ratio, spatial distribution, maturity and reproductive period. Crabs and environmental factors (i.e., water temperature and salinity, and sediment texture and organic matter content) were collected monthly, from July 2012 to June 2014 in four sites within the Federal Environmental Protection Area of Cananeia-Iguape-Peruibe: located in the oceanic area adjacent to the Cananeia region. The population had a female-biased sex-ratio. Persephona punctata had a seasonal reproduction and the higher percentage of ovigerous females (OF) occurred in spring and summer. There was a positive correlation (lag 0) between temperature and number of OF (cross-correlation, p < 0.05) and a negative correlation between salinity and OF (lag-2), suggesting that periods of higher salinity may be favorable to larval hatching. The estimated size (carapace width - CW50) at the onset of gonadal maturity of males (35.0 mm) was larger than that of females (30.1 mm), which is a common feature of Brachyura. Our results extend the knowledge on the life history of P. punctata and may be useful for the development of future mitigation measures aimed at its conservation.
Keywords: Reproductive period; sexual maturity; sex-ratio; population dynamics; Western Atlantic